2000
DOI: 10.1002/(sici)1096-8652(200006)64:2<112::aid-ajh7>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic effects of low-dose protamine following cardiopulmonary bypass

Abstract: Twenty-eight patients undergoing cardiac surgery were prospectively studied and were assigned to two groups. The patients received 0.8-(Group L) or 2.0-fold (Group H) dose of protamine for the neutralization after cardiopulmonary bypass (CPB) which was determined by Hepcon HMS assay system in which the reagent chamber containing the concentration of protamine that completely neutralized the heparin had the shortest clotting time. Mean dose of protamine was 1.60 ± 0.50 mg kg −1 in Group L, and 3.56 ± 1.48 mg kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
(23 reference statements)
1
8
0
1
Order By: Relevance
“…However, the parallel HTC testing with heparinase excluded that the slight postoperative increase in ACT in both groups was caused by remaining heparin. Data from this study support previous studies [14][15][16] that advocate a low-dose protamine regime to avoid the possible drawbacks of the drug. Furthermore, both The Society of Thoracic Surgeons and The Society of Cardiovascular Anesthesiologists recommend a low-dose protamine regime in their Clinical Practice Guidelines.…”
Section: Discussionsupporting
confidence: 89%
“…However, the parallel HTC testing with heparinase excluded that the slight postoperative increase in ACT in both groups was caused by remaining heparin. Data from this study support previous studies [14][15][16] that advocate a low-dose protamine regime to avoid the possible drawbacks of the drug. Furthermore, both The Society of Thoracic Surgeons and The Society of Cardiovascular Anesthesiologists recommend a low-dose protamine regime in their Clinical Practice Guidelines.…”
Section: Discussionsupporting
confidence: 89%
“…In a small prospective study, randomisation of patients to a 0.8 vs 2.0 protamine-to-heparin dosing ratio revealed that high protamine dosing was associated with changes in platelet count and PF4, whilst post-protamine ACT levels were similar amongst groups. 81 In a randomised controlled trial in coronary artery bypass graft (CABG) patients, we showed that a protamine-to-heparin dosing ratio of 1. .021] when compared with a protamine-toheparin dosing ratio of 0.8, respectively.…”
Section: Ratio-based Dosingmentioning
confidence: 99%
“…6,7,24,25 To determine the relative importance of protamine inhibition of FV activation in mediating the anticoagulant effect of protamine in plasma, increasing concentrations of either FV or FVa (0-20 nM) were titrated into FV-deficient plasma in the presence or absence of protamine (30 g/mL; Figure 7). In a TF-initiated thrombin generation assay, addition of FV or FVa resulted in a significant increase in thrombin generation ( Figure 7A-B).…”
Section: Preactivation Of Fv Eliminates Protamine Anticoagulant Effecmentioning
confidence: 99%